Correlation between Crystallinity, Charge Transport, and Electrical Stability in an Ambipolar Polymer Field-Effect Transistor Based on Poly(naphthalene-alt-diketopyrrolopyrrole) - Kim, Beom Joon; Lee, Hyo-Sang; Lee, Joong Seok; Cho, Sanghyeok; Kim, Hyunjung; Son, Hae Jung; Kim, Honggon; Ko, Min Jae; Park, Sungnam; Kang, Moon Sung; Oh, Se Young; Kim, BongSoo; et al. (American Chemical Society, 2013)
We characterized the electrical properties of ambipolar polymer field-effect transistors (PFETs) based on the low-band-gap polymer, pNAPDO-DPP-EH. The polymer consisted of electron-rich 2,6-di(thienyl)naphthalene units with decyloxy chains (NAPDO) and electron-deficient diketopyrrolopyrrole units with 2-ethylhexyl chains (DPP-EH). The as-spun pNAPDO-DPP-EH PFET device exhibited ambipolar transport properties with a hole mobility of 3.64 X 10(-3) cm(2)/(V s) and an electron mobility of 0.37 X 10(-3) cm(2)/(V s). Thermal annealing of the polymer film resulted in a dramatic increase in the carrier mobility. Annealing at 200 degrees C yielded hole and electron mobilities of 0.078 and 0.002 cm(2)/(V s), respectively. The mechanism by which the mobility had improved was investigated via grazing incidence X-ray diffraction studies, atomic force microscopy, and temperature-dependent transport measurements. These results indicated that thermal annealing improved the polymer film crystallinity and promoted the formation of a longer-range lamellar structure that lowered the thermal activation energy for charge hopping. Thermal annealing, moreover, reduced charge trapping in the films and thus improved the electrical stability of the PFET device. This work underscores the fact that long-range ordering in a crystalline polymer is of great importance for efficient charge transport and high electrical stability.
Keywords: THIN-FILM TRANSISTORS; HIGH-PERFORMANCE; HIGH-MOBILITY; SEMICONDUCTING POLYMERS; N-CHANNEL; DESIGN; COPOLYMERS; CIRCUITS; HOLE